2013
DOI: 10.1016/j.vetpar.2013.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Feline thelaziosis caused by Thelazia callipaeda in Portugal

Abstract: 25Thelazia callipaeda (Spirurida, Thelaziidae) is a nematode that lives in the conjunctival 26 sac of domestic and wild carnivores, rabbits and humans. causing mild to severe 27 symptoms (e.g., conjunctivitis, lacrimation, epiphora, blepharospasm, keratitis and even

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…Detection of the eyeworm in animals that had never travelled abroad indicates of autochthonous presence of thelaziosis in Serbia as it was previously recorded by other authors in endemic areas similar in geographic position, altitude and fi eld confi guration to those in our study [5,[8][9][10][13][14][15]26]. In addition, distances between localities (from 16 to 146 km air distance) and the affected area (about 12390 km 2 ) in our study indicate the endemic nature of thelaziosis in Serbia.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Detection of the eyeworm in animals that had never travelled abroad indicates of autochthonous presence of thelaziosis in Serbia as it was previously recorded by other authors in endemic areas similar in geographic position, altitude and fi eld confi guration to those in our study [5,[8][9][10][13][14][15]26]. In addition, distances between localities (from 16 to 146 km air distance) and the affected area (about 12390 km 2 ) in our study indicate the endemic nature of thelaziosis in Serbia.…”
Section: Discussionsupporting
confidence: 86%
“…The number of parasites per animal (7 to 150) in our study was greater than reported by other researchers (from 1 to 76) [10,[13][14][15]26]. The highest parasite burden was observed in a 8-years-old hunting dog (harbouring totally 150 parasites).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Reports of thelaziosis in cats have been significantly rarer. The prevalence of infection by this Thelazia in cats is lower, since they are less exposed to the population of intermediate hosts (17,25,37).…”
Section: Resultsmentioning
confidence: 99%
“…This zoonotic parasite that lives in the conjunctival sac, under the lids and the nictitating membrane of dogs, cats and wildlife, may induce a range of clinical signs, such as epiphora, photophobia, keratisis, conjunctivitis, etc. (Otranto and Traversa 2005;Otranto et al 2009;Soares et al 2013;Maia et al 2014;Motta et al 2014).…”
Section: Introductionmentioning
confidence: 99%